Institutional and Individual Sentiment: Smart Money and Noise Trader Risk - Maik Schmeling (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
Using a new data set on investor sentiment we show that institutional and individual sentiment proxy for smart money and noise trader risk, respectively. First, using bias-adjusted long-horizon regressions, we document that institutional sentiment forecasts stock market returns at intermediate horizons correctly, whereas individuals consistently get the direction wrong. Second, VEC models show that institutional sentiment forecasts mean-reversion whereas individuals forecast trend continuation. Finally, institutional investors take into account expected individual sentiment when forming their expectations in a way that higher (lower) expected sentiment of individuals lowers (increases) institutional return forecasts. Individuals neglect the information contained in institutional sentiment.
Keywords: G14; G12; G11; 330; investor sentiment; predictive regressions; noise trader; smart money